IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA ANAK BERKEBUTUHAN KHUSUS (DIFABEL) PADA MASA PANDEMI COVID-19 - Nurhasanah, Neneng; Rukajat, Ajat; Arifin, Zaenal (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
IMPLEMENTATION OF ISLAMIC RELIGIOUS EDUCATION LEARNING FOR CHILDREN WITH SPECIAL NEEDS (DISABLED) DURING THE COVID-19 PANDEMICThis study aims to determine the extent to which PAI has been implemented in children with special needs during the COVID 19 pandemic. It has been almost fifteen months since we have been hit by the COVID 19 pandemic which has had a significant impact on major changes in the world of education throughout the world, including Indonesia. During the pandemic, everyone began to adjust to the technology used to support the learning process during the COVID 19 pandemic. The COVID 19 pandemic period itself provides challenges as well as problems for all elements of education including parents, teachers and students. In particular, teachers are required to find a learning model formulation that is effective, efficient and can be understood by all students today. The research method used is an analytical method with a qualitative approach. The research process includes making research questions and procedures that are still provisional in nature, collecting data on preparatory settings, inductive data analysis, building partial data into themes, and then providing interpretations of the meaning of data. The final activity is to build reports into a flexible structure. The research subjects themselves took the Alam Amani Private Elementary School, Karawang. This research shows that the implementation of Islamic Education learning for children with special needs during the COVID 19 pandemic, in addition to adjusting the children's abilities, it also adapts to the parents' abilities because it must be admitted that providing teaching to students with special needs has its own challenges.